Combined application of dexamethasone and hyperbaric oxygen therapy yields better efficacy for patients with delayed encephalopathy after acute carbon monoxide poisoning - Xiang, Wenping (Drug Des Devel Ther, 2017)
BACKGROUND: Delayed encephalopathy after acute carbon monoxide (CO) poisoning (DEACMP) commonly occurs after recovering from acute CO poisoning. This study was performed to assess the efficacy of the combined application of dexamethasone and hyperbaric oxygen (HBO) therapy in patients with DEACMP. PATIENTS AND METHODS: A total of 120 patients with DEACMP were recruited and randomly assigned into the experimental group (receiving dexamethasone 5 mg/day or 10 mg/day plus HBO therapy) and control group (HBO therapy as monotherapy). Meanwhile, the conventional treatments were provided for all the patients. We used the Mini-Mental State Examination (MMSE) scale to assess the cognitive function, the National Institutes of Health Stroke Scale (NIHSS) to assess the neurological function and the remission rate (RR) to assess the clinical efficacy. Myelin basic protein (MBP) in the cerebrospinal fluid (CSF) was also measured. RESULTS: After 4 weeks of treatment, compared to the control group, the experimental group had a significantly higher remission rate (P=0.032), a significantly higher average MMSE score (P=0.037) and a significantly lower average NIHSS score (P=0.002). Meanwhile, there was a trend toward better improvement with dexamethasone 10 mg/day, and the level of MBP in the CSF of patients was significantly lower in the experimental group than in the control group (P<0.0001). The addition of dexamethasone did not significantly increase the incidence of adverse events. CONCLUSION: These results indicate that the combined application of dexamethasone and HBO therapy could yield better efficacy for patients with DEACMP and should be viewed as a potential new therapy.